Perancangan dan Implementasi Sistem Informasi Gereja Kristen Jawa Plengkung Berbasis Web Menggunakan Framework CodeIgniter - Donny Julianto Setiawan Halim; Ramos Somya (KITA Institute, 2023)
Information system is one of the thing that can be called as mandatory to be had by an institution right now. Gereja Kristen Jawa Plengkung (GKJP) is still using all of its record by traditional way. Data saved by tradisional way can caused a duplication of data called redundancy. With the existence of information system, activities in GKJP like data saving are expected to go well for the future. In the making of information system, waterfall is used as the research method for the development of information system. Waterfall usually has steps like (1) analytic, (2) design, (3) coding, (4) testing, (5) support. Based on the research and the testing that has been done, design and implementation of information system in Gereja Kristen Jawa Plengkung with Web as its base and the using of CodeIgniter Framework can be called success because it can fulfill the requirement suggested by the user.